Association of CSF and PET markers of neurodegeneration with electroclinical progression in Lafora disease - d'Orsi, Giuseppe; Farolfi, Andrea; Muccioli, Lorenzo; Palumbo, Orazio; Palumbo, Pietro; Modoni, Sergio; Allegri, Vincenzo; Garibotto, Valentina; Di Claudio, Maria Teresa; Di Muro, Ester; Benvenuto, Mario; Bisulli, Francesca; et al. (Frontiers in Neurology, 2023)
Purpose To evaluate the electro-clinical features in association with laboratory and instrumental correlates of neurodegeneration to detect the progression of Lafora disease (LD). Methods We investigated the electro-clinical longitudinal data and CSF Aβ42, p-tau181 and t-tauAg, amyloid, and 18F-FDG PET of five unrelated LD families. Results Three progressive electro-clinical stages were identified. The early phase was characterized by rare, generalized tonic-clonic and focal visual seizures, followed by the occurrence of myoclonus after a period ranging from 2 to 12 months. The intermediate stage, usually occurring 2 years after the onset of epilepsy, is characterized by a worsening of epilepsy and myoclonus associated with progressive dementia and cerebellar signs. Finally, the late stage, evolving after a mean period of 7 ± 1.41 years from the onset of the disease, was characterized by gait ataxia resulting in bedriddenness, severe dementia, daily/pluri-daily myoclonus, drug-resistant epilepsy, clusters of seizures or status epilepticus, and medical complications. Amyloid (CSF Aβ42, amyloid PET) and neurodegenerative (CSF p-tau181 and t-tauAg, FDG-PET) biomarkers indicate a pattern of cognitive impairment of the non-Alzheimer's disease type. A total of 80% of the LD patients showed more severe hypometabolism in the second FDG-PET scan compared to the first scan performed in a lower phase; the lateral temporal lobe and the thalamus hypometabolism were associated with the presence of intermediate or late phase. Conclusions Three electroclinical and 18F-FDG PET evolutive stages are useful biomarkers for the progression of LD and could help to evaluate the efficacy of new disease-modifying treatments. The combination of traditional CSF biomarkers improves the diagnostic accuracy of cognitive decline in LD patients, indicating a cognitive impairment of the non-Alzheimer's disease type.